Persepsi Kelompok Orang dengan Kondisi Penyerta Komorbid Hipertensi terhadap Pelayanan Vaksinasi COVID-19 - Ardiansyah Ardiansyah; Indri Puji Lestari (Jurnal Keperawatan Silampari, 2023)
This study aims to see how groups of people with hypertension comorbid conditions perceive the COVID-19 vaccination service. The research design uses qualitative methods with a phenomenological approach. The results of this study indicate that all participants claimed to want to be vaccinated but were influenced by several obstacles, especially the participants' health conditions; participants considered vaccination a requirement for administrative purposes, public activities, and others. Participants assessed that there was an element of coercion to make it mandatory in the implementation of COVID -19. In conclusion, the perception of groups of people with comorbid conditions of hypertension towards COVID-19 vaccination services produces four main themes, namely Knowledge of COVID-19 vaccination, barriers to receiving COVID-19 vaccination, mandatory vaccination as a condition for carrying out public activities, government policy towards implementation COVID-19 vaccination. Keywords: COVID-19, Hypertension, Comorbid, Vaccines